(untitled) (Dermatology Reports, 2025)
Vismodegib and sonidegib are smoothened (SMO) inhibitors approved for the treatment of advanced basal cell carcinoma (aBCC). This study investigates the real-world experiences and outcomes associated with these therapies across multiple Italian centers. A retrospective, observational, multicenter study was conducted. Medical records of patients with local advanced basal cell carcinoma (laBCC) treated with SMO inhibitors outside of clinical trials from July 2019 to April 2024 were analyzed. A total of 57 patients were included in the study, with 19 (33.3%) receiving vismodegib and 38 (66.7%) receiving sonidegib. Vismodegib demonstrated a complete response (CR) in 31.6% of cases and a partial response (PR) in 26.3%. Sonidegib achieved a CR of 47.4% and a PR of 36.8%. The median treatment duration was 8 months for vismodegib and 12 months for sonidegib. Adverse events were more frequently reported with vismodegib. Treatment interruption due to adverse events occurred in 47.4% of vismodegib recipients and in 13.2% of those receiving sonidegib. The progression of the disease under treatment occurred in 7.9% of cases of patients under sonidegib and in 26.3% of cases under vismodegib. *************************************************************** *Appendix Authors list Valentina Benzecry Mancin,1 Veronica Benzi,2 Matteo Bianco,2,3 Alessandra Bulotta,4 Antonio Costanzo,2,3 Giuseppe Damiano,5 Nerina Denaro,6 Laura Eibenschutz,7 Barbara Merelli,8 Giulia Murgia,1 Alessandra Narcisi,3 Emanuela Passoni,1 Francesco Piscazzi,2,3 Vincenzo Russo5 1Dermatology Unit, Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico, Milan; 2Department of Biomedical Sciences, Humanitas University, Pieve Emanuele, Milan; 3Dermatology Unit, IRCCS Humanitas Research Hospital, Rozzano, Milan; 4Department of Oncology, IRCCS San Raffaele, Milan; 5Unit of Immuno-Biotherapy of Melanoma and Solid Tumors, IRCCS Ospedale San Raffaele, Milan; 6Oncology Unit, Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico, Milan; 7Oncologic and Preventive Dermatology Unit, IFO-San Gallicano Dermatological Institute IRCCS, Rome; 8Oncology Unit, ASST Papa Giovanni XXIII, Bergamo, Italy